2020
DOI: 10.1186/s12992-020-00609-9
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS research in Africa and the Middle East: participation and equity in North-South collaborations and relationships

Abstract: Background HIV/AIDS has attracted considerable research attention since the 1980s. In the current context of globalization and the predominance of cooperative work, it is crucial to analyze the participation of the countries and regions where the infection is most prevalent. This study assesses the participation of African countries in publications on the topic, as well as the degree of equity or influence existing in North-South relations. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…This finding suggests that there is still some way to go before principles of fairness are embedded in practice and is consistent with claims that the system of global health remains colonial at its core [ 33 ]. Inequities experienced by participants included only being invited to participate in a study after the research concept and design had been determined [ 10 ], being offered only a limited role [ 1 , 17 ], receiving fewer benefits than HIC partners [ 36 , 38 ], HIC partners interfering in the LMIC institution’s operations [ 12 , 39 ] and HIC partners over-claiming authorship positions [ 16 , 18 ]. Several less well documented challenges also emerged which had arisen when LMIC institutions were in the lead partner role.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that there is still some way to go before principles of fairness are embedded in practice and is consistent with claims that the system of global health remains colonial at its core [ 33 ]. Inequities experienced by participants included only being invited to participate in a study after the research concept and design had been determined [ 10 ], being offered only a limited role [ 1 , 17 ], receiving fewer benefits than HIC partners [ 36 , 38 ], HIC partners interfering in the LMIC institution’s operations [ 12 , 39 ] and HIC partners over-claiming authorship positions [ 16 , 18 ]. Several less well documented challenges also emerged which had arisen when LMIC institutions were in the lead partner role.…”
Section: Discussionmentioning
confidence: 99%
“…Attention to this seems to be lower in Italy ( 23 ) and in western European countries, other than the United Kingdom ( 24 ). The majority of studies have been from the United States ( 25 ), aside those from Sub-Saharan Africa ( 26 ). In the latter, although patterns of HIV testing utilization vary from group to another (e.g., gender, age category) ( 27 ), a universal awareness and a very high level of HIV knowledge attributable to sustained health education programs, have been shown ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 5.8% of PLWH are in western/central Europe or North America, whereas 67.7% of PLWH are in Africa or the Middle East [ 4 ]. Despite this, a review of 68,808 studies found that over 80% of research into HIV published between 2010–2017 was produced in North America and Europe [ 5 ]. Authorship of HIV research is clustered in high-income countries in North America and Europe [ 6 ], whereas the greatest burden of HIV infection lies in the Global South, where access to latest-generation cART and psychological healthcare is also limited.…”
Section: Inequity In Hiv Mental Health Researchmentioning
confidence: 99%